Electronic structure and Slater-Pauling behaviour in half-metallic Heusler alloys calculated from first principles - Galanakis, I.; P. Mavropoulos; P.H. Dederichs (JOURNAL OF PHYSICS D-APPLIED PHYSICS, 2006)
Intermetallic Heusler alloys are amongst the most attractive half-metallic systems due to their high Curie temperatures and their structural similarity to binary semiconductors. In this review we present all overview of the basic electronic and magnetic properties of both Heusler families: the so-called half-Heusler alloys like NiMnSb and the full-Heusler alloys like Co2MnGe. Ab initio results suggest that both the electronic and magnetic properties ill these compounds are intrinsically related to the appearance of the minority-spin gap. The total spin magnetic moment M-t scales linearly with the number of the valence electrons Z(t), such that M-t = Z(t) - 24 for the full-Heusler and M-t = Z(t) - 18 for the half-Heusler alloys, thus opening the way to engineer new half-metallic alloys with the desired magnetic properties.